Mercerization of Agricultural Waste: Sweet Clover, Buckwheat, and Rapeseed Straws - Madara Žiganova; Agnese Ābele; Zanda Iesalniece; Remo Merijs Meri (Fibers, 2022)
This research presents the alkali treatment effect on three types of agricultural residues: sweet clover (SCS), buckwheat (BS), and rapeseed straws (RS). The aim of the study was to find the optimal treatment conditions for each straw type, and to assess the potential of sweet clover straw as reinforcement for polymer composites in comparison to buckwheat and rapeseed. The straws were ground and treated for 15, 30, and 60 min using NaOH at concentrations of 2, 5, and 10%. To investigate the treatment results on the SCS, BS, and RS fibers, Fourier transform infrared spectroscopy, scanning electron microscopy, optical microscope, X-ray diffraction, and thermogravimetric analysis were used. Results indicate that the optimal room-temperature alkaline-treatment conditions of SCS fibers were the same as those for RS treated with 2% NaOH solution for 30 min. These conditions were milder in comparison to those used for the treatment of BS: 60 min in a 5% NaOH solution. During the treatment, noncellulosic substances were largely removed, and the aspect ratio of the fibers was increased, and the destruction temperature, crystallinity, and morphology were also affected. Consequently, SCS has promising potential for use in polymer composites.